Dampak Pertumbuhan Penduduk terhadap Lingkungan di Kabupaten Tangerang - Amalia Zahra Khairani; Silvia Kamelia Hermawati; Akrom Akrom (PT. Saha Kreasi Indonesia, 2026)
This research discusses the environmental impacts caused by uncontrolled population growth in Tangerang Regency, Banten Province, which serves as a buffer zone for the Jakarta metropolitan area. The study aims to analyze five main aspects: population growth dynamics, impacts on water resources and river pollution, land conversion and loss of green cover, air quality deterioration and waste management problems, as well as policy evaluation based on environmental carrying capacity. The method used is a qualitative descriptive approach through literature review and secondary data analysis. The findings reveal that the population growth rate reaches 2.8 percent per year, dominated by migration of tens of thousands of people annually, leading to uneven population density ranging from 1,340 to 9,614 people per square kilometer. Consequently, Tangerang Regency experiences land subsidence, river pollution in Ciujung and Cisadane, conversion of approximately 700 hectares of rice fields per year, high rates of acute respiratory infections due to poor air quality, and an overcapacity final disposal site at Rawa Kucing. This research recommends spatial planning reform, green infrastructure development, and sustainable waste management based on environmental carrying capacity.